2017
DOI: 10.1051/matecconf/201710303009
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder’s Perspective on Risks Allocation in Design and Build Projects in Malaysia

Abstract: Abstract. Design and Build (DB) projects are prone with high risks. The appropriate risk allocation among contracting parties in Design and Build (DB) projects is an important and essential decision leading to the project performance. The establishment of risk allocation at early stage of the projects will contribute great impact to the project objective. It is required judgement and experiential knowledge of the construction experts to determine the appropriateness of risk allocation to the parties involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…D-B construction is considered unique as only one entity is contracted to perform the design and construction activities (Yu et al , 2017). The contractors take responsibility for the project's design and construction (Saaidin et al , 2017). Elevated construction project intensity is the unique feature of D-B-based construction, in addition to a reduction in delivery time and achievement of efficacy, as foremost features (Yu et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…D-B construction is considered unique as only one entity is contracted to perform the design and construction activities (Yu et al , 2017). The contractors take responsibility for the project's design and construction (Saaidin et al , 2017). Elevated construction project intensity is the unique feature of D-B-based construction, in addition to a reduction in delivery time and achievement of efficacy, as foremost features (Yu et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Achieving success in D-B construction projects at a national level is a problem, as it requires economic stability, efficiency, quality and transparent policies. D-B studies undertaken in the Malaysian construction industry have highlighted success factors that influence time and cost overruns, including behavioural aspects of project management (Ullah et al , 2018) and stakeholder perspective on the allocation of risks (Saaidin et al , 2017). Moreover, studies have also investigated the success factors for hospital D-B projects (Isa et al , 2011), public infrastructure projects (Yap et al , 2019) and public construction of residential projects in Malaysia (Lee et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the perspectives of professional quantity surveyors on factors that affect construction costs at the tender stage showed that the overall project cost will be affected by the design information produced by consultants (Adafin et al, 2016). A balanced view is needed by gathering opinions from both the client and design team stakeholders, and the production stakeholders comprising the contractor and supply chain (Tarhini et al, 2015;Saaidin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%